Sistema informático web de gestión de los grifos de la dirección técnica de hidrocarburos de la DREM-Loreto - García Montalván, Víctor Junior (2022)
The general objective of the work was to develop a web computer system to improve the management of taps of the technical direction of hydrocarbons of the DREMLoreto, as specific objectives: to verify that the web computer system will improve the times for obtaining information from the taps of the region, response times in generating reports and resolution generation times. It has a quantitative approach, according to the level of the investigation it is technological application, according to the researcher's intervention it is pre-experimental, the number of measurements is cross-sectional, according to the data collection planning it is prospective, the study population is the recording times of the operations carried out to measure the dependent variable, the sample design was carried out from the total population, the data collection procedure was the observation method, using an observation sheet for this, the information processing was carried out with the software statistical SPSS, checking the improvement in reducing management time, using the software, demonstrating in the results; the time to obtain information, decreased by an average of 77.80%, in regard to the response time in the generation of reports, it was reduced by 61.78%; In addition, the resolution generation time decreased by 97.56%, demonstrating the effectiveness of the designed software.